Analisis Proyek Konstruksi pada Sektor Minyak dan Gas Menggunakan Pendekatan ISO 21500:2021: Studi Kasus PT PGAS Solution - M Fanshurullah Asa; Regina Intan Junita (Department of Civil Engineering, Diponegoro University, 2025)
PT PGAS Solution, as a certified construction company in Indonesia, applies ISO 21500:2021 as a guideline for managing its project activities, and this study aims to evaluate the level and effectiveness of its implementation while identifying the key obstacles encountered in practice. A quantitative descriptive–explanatory approach was employed using a questionnaire based on the ten core subjects outlined in ISO 21500:2021 Clause 7, which was distributed to 20 project personnel through a saturated sampling method, with data analyzed using descriptive statistics, validity and reliability tests, assumption testing, and multiple linear regression. The results indicate that the overall implementation level falls into the “Fairly Good” category, with an average score of 19.795, and the instrument demonstrates strong reliability, as evidenced by a Cronbach’s Alpha value of 0.938. Furthermore, regression analysis shows that information and documentation management has the most significant positive influence on system implementation, while procurement and lessons learned contribute negatively due to challenges in process optimization and organizational knowledge retention, with an adjusted R² value of 69.7% indicating a moderately strong model fit in explaining the variation in implementation levels. These findings highlight the need for improved procurement systems, stronger institutional learning mechanisms, and enhanced integration of ISO 21500:2021 practices to strengthen project delivery performance within the oil and gas construction sector.